Security Analysis and Encryption Time Comparison Description on Cryptography Advanced Encryption Standard (AES) - Taufiqqurrachman, Taufiqurrachman; Elsandi, Dani (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
AES is a cryptographic computation intended to work on 128bit, 192bit, and 256bit message blocks. The four main calculation procedures consist of a process (ShiftRows) and three substitution processes (SubBytes, MixColumns, and AddRoundKey). The AES encryption procedure is intended to perform encryption confidentially with a non-linear level of security with time complexity as effectively as possible, using a light change procedure in its implementation. On the other hand, the inverse of this procedure has low effectiveness, so the AES description procedure is slow. By examining the calculations, it was found that AES has complexity in the O(n) level for both encryption and decryption procedures. From a security check, AES has a very high level of security. From the speed correlation test results, it can be concluded that AES has a high level of effectiveness. Meanwhile, through testing encryption versus description, it can be understood that from timeliness, encryption is not equivalent to description, with the effectiveness of description being quite low.